IMPOLITENESS STRATEGIES USED BY SUPPORTERS AND DETRACTORS OF AHOK IN THEIR ONLINE COMMENTS BY GENDER - Vini Mara Shinta; Hamzah Hamzah; Delvi Wahyuni (Universitas Negeri Padang, 2018)
The purpose of this study was to find impoliteness strategies used by supporters and detractors of Ahok differed by their gender in their online comments based on Culpeper’s theory (1996). This research was descriptive qualitative research based on impoliteness strategies phenomena in written language. The data on this research were words, phrases, and sentences in online comments that contained impoliteness strategies found in social media, Facebook and Instagram, collected from January to October 2017. The instruments of this research were Wi-Fi, laptop, writing equipment, and indicators of impoliteness strategies. The results of analysis showed that from 300 comments collected, there were 584 impoliteness strategies found. The reason why number of strategies found bigger than the data collected is because the commentators mostly performed more than one strategy in one utterance. Four by five strategies found in this research were bald on record, positive impoliteness, negative impoliteness, and sarcasm or mock politeness. The strategies that were not found was withhold politeness because it only occurred in spoken language. The most used strategies was positive impoliteness. The highest user of positive impoliteness was male detractors (52%).